Case study of an evaluation coaching model: Exploring the role of the evaluator. (April 2015) - Ensminger, David C.; Kallemeyn, Leanne M.; Rempert, Tania; Wade, James; Polanin, Megan
Highlights: Evaluation coaching is a viable option for non-profits with limited budgets. Evaluation coaching promotes dialogue and clarifies values, beliefs and knowledge. Evaluation coaching contributes to organizational learning and capacity building. We added results and developmental coaching to capacity building literature. Abstract: This study examined the role of the external evaluator as a coach. More specifically, using an evaluative inquiry framework (Preskill & Torres, 1999a; Preskill & Torres, 1999b ), it explored the types of coaching that an evaluator employed to promote individual, team and organizational learning. The study demonstrated that evaluation coaching provided a viable means for an organization with a limited budget to conduct evaluations through support of a coach. It also demonstrated how the coaching processes supported the development of evaluation capacity within the organization. By examining coaching models outside of the field of evaluation, this study identified two forms of coaching — results coaching and developmental coaching — that promoted evaluation capacity building and have not been previously discussed in the evaluation literature.